A Mathematical Approach to a More Accurate Determination of Critical Micelle Concentration and Other Thermodynamic Parameters of 14‐2‐14 Gemini Surfactant in Water–Organic Solvent Mixed Media at Variable Temperatures. Issue 1 (8th November 2016) - Sood, Ashwani Kumar; Pritambir,; Aggarwal, Meenu
Abstract: To explore how the solvent characteristics influence the self‐aggregation of the cationic gemini surfactant dimethylene‐1, 2‐bis(tetradecyldimethylammonium bromide) (14‐2‐14) and to obtain various energetic parameters, conductometric experiments were performed on the binary mixtures in the presence of commonly used organic solvents; formamide (FA), acetonitrile (AN) and 2‐methoxyethanol (ME) in aqueous solutions at varying temperatures (298.15–323.15 K) and compositions. The procedure suggested by Carpena et al. has been utilized to analyze conductivity–concentration plots in order to obtain critical micelle concentration (CMC) and degree of counterion dissociation (α) of the micelles. This method provides more accurate results as compared to conventional treatments, and the experimental error for the evaluation of micellar parameters is reduced significantly. The results revealed that, although the process of micellization becomes less favorable with the increase in composition of FA, AN and ME in mixed systems, the increase in CMC at compositions lower than 20% (v/v) of the organic solvents is relatively less, indicating that water character is dominant in the bulk phase. As the enthalpy of micellization became more negative, the corresponding entropy change became less positive and enthalpy–entropy compensation phenomenon has been observed for 14‐2‐14 in all the mixtures within the studied temperature range.